LUCIO FONTANA AND ARCHITECTURE - Ferriani, Barbara (Protection of Cultural Heritage, 2019)
Lucio Fontana’s collaboration with architects, which continued to progress over the entire period of his creative experience along with his more famous artistic and spatial production, offered important opportunities for experimentation and research. The artist worked with architects such as Luigi Figini, Gino Pollini, Giò Ponti, Luciano Baldessari, Marco Zanuso, Osvaldo Borsani and Ico Parisi, and it was actually the architects who first intuited the innovative scope of his research. It involved works of a temporary nature carried out for exhibitions, trade fairs and celebrations of historical events, some of which went missing at the end of the events, but also some that became an integral part of extant architecture. Indeed, the artist made numerous environmental works for public buildings, hotels, cinemas and private homes, using traditional materials such as ceramics, mosaics and plaster, as well as new media such as fluorescent colours, black lights, neon lights, and more. As often happens, and as needs and tastes changed, the works were decontextualized and assumed a different connotation. Here below is a description of the choices made during three of the seven restorations we carried out in the last few years on environmental works created by Fontana between the mid-1940s and the end of the 1950s, which were taken from their original location and moved to new sites.